Analisis Pengaruh Inflasi dan Kurs Terhadap Indeks Harga Saham Gabungan (IHSG) - Muhammad Fathul Ilmi Al-Hanif; Fauzia Rahma Qurrota’aini; Navisatul Muna; Hanifah Ratih Prastiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to see the effect of inflation and exchange rates on the Composite Stock Price Index (IHSG). The object of this research is the Composite Stock Price Index (IHSG). The subject of this research is Inflation in 1999. The data used is time series data. The data analysis method used is a linear regression with a significant level of 0.05. The dependent variable in this study is the mixed stock price index (IHSG), while the independent variables in this study are inflation and the rupiah exchange rate. based on data analysis, inflation has an effect on the JCI as evidenced by the inflation regression coefficient of -3,212.908 with a significance value of 0.0462. The exchange rate has a positive and significant effect on the JCI as evidenced by the exchange rate regression coefficient of 0.699 with a significance value of 0.0. while the coefficient of determination is 0.765. This shows that 76.5% of the variation in the JCI dependent variable can be explained by the independent variables of inflation and exchange rates, while the remaining 23.5% is explained by other variables outside the research model.